2021
DOI: 10.1371/journal.pone.0246525
|View full text |Cite
|
Sign up to set email alerts
|

Health and well-being of trans and non-binary participants in a community-based survey of gay, bisexual, and queer men, and non-binary and Two-Spirit people across Canada

Abstract: There is a paucity of population health data on the experiences of transgender, non-binary, and other gender minority gay, bisexual, and queer men, and Two-Spirit people in Canada. To address this gap, this article presents a socio-demographic and health profile of trans and non-binary participants from the community-based bilingual 2018 Sex Now Survey. Participants were recruited in-person from Pride festivals in 15 communities to self-complete an anonymous paper-and-pen questionnaire. To be eligible, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…These findings, together with those regarding low resilience, support the view that NBG individuals were more vulnerable to the stress caused by the Covid-19 pandemic and its consequences than BG participants, suffered from increased psychic symptoms and consequently, decreased FUNCT. Non-binary individuals represent a disadvantageous, marginalised minority, being at risk of victimisation and discrimination stress (Rutherford et al 2021; Schmits et al, 2021). Thus, it is understandable that additional social stress related to Covid-19 pandemic had so detrimental effect on their every-day FUNCT and that NBG individuals may need a special attention and support during ongoing and future pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…These findings, together with those regarding low resilience, support the view that NBG individuals were more vulnerable to the stress caused by the Covid-19 pandemic and its consequences than BG participants, suffered from increased psychic symptoms and consequently, decreased FUNCT. Non-binary individuals represent a disadvantageous, marginalised minority, being at risk of victimisation and discrimination stress (Rutherford et al 2021; Schmits et al, 2021). Thus, it is understandable that additional social stress related to Covid-19 pandemic had so detrimental effect on their every-day FUNCT and that NBG individuals may need a special attention and support during ongoing and future pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…However, Matijczak and colleagues [ 60 ] found that gender and sexual minority (GSM) respondents were not more likely to delay or avoid testing/treatment for COVID-19, as compared to their non-GSM counterparts. Rutherford and colleagues [ 16 ] found that trans participants ( n = 446) were more likely to report both being vaccinated for HPV and being denied the HPV vaccination than the sexual minority cis men ( n = 3083) in the sample. Future research should examine whether trans individuals experienced barriers to receiving COVID-19 vaccinations and policy/practice shifts ensuring these barriers are not reproduced in the future must be made.…”
Section: Discussionmentioning
confidence: 99%
“…Despite documented increased risk factors, including heightened risk for HIV, HPV, and other conditions [ 14 , 15 , 16 ], trans individuals may avoid seeking medical attention. Nearly a quarter of respondents in the U.S. Trans Survey reported not seeing a doctor when they needed to for fear of being mistreated [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following SGM youth–specific recruitment recommendations from previous studies [ 11 , 23 ], our team designed the study’s website, social media campaigns, and distribution materials to emphasize the research project’s larger goal of contributing evidence toward efforts to make SGM youth feel safe and included ( Figure 1 ). The promotional materials were distributed in French and English.…”
Section: Methodsmentioning
confidence: 99%